2018
DOI: 10.3846/transport.2018.1570
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Public Transport Users’ Satisfaction Using Quality Function Deployment: Belgrade Case Study

Abstract: This paper presents a case study using Quality Function Deployment (QFD) method to identify urban public transport users’ needs and requests and to improve service quality in urban public passenger transport in Belgrade. In order to determine users’ satisfaction, a direct interview – survey a sample of 15000 of urban public passenger transport system users, according to the defined questionnaire has been performed. Results of these interviews are used as input in the first stage of QFD method. An overall unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 27 publications
0
8
0
4
Order By: Relevance
“…Upon analyzing transit service quality based on cluster analysis, frequency and punctuality were found to be the most important attributes, whereas accessibility was identified as a variable having limited relevance for users in Granada, Spain ( 5 ). Bajčetić et al used the quality function deployment method to identify urban public transport users’ needs related to public transport in Belgrade, and concluded that service reliability, frequency, and vehicle elements need to be considered carefully for improving the quality of public transport travel ( 17 ). Saw et al studied passenger satisfaction toward metro infrastructures, facilities, and services in the Tyne and Wear Metro, UK, and found ticket cost, general cleanliness of station, condition of station, and cleanliness inside the train to have performed inadequately from a user perspective ( 18 ).…”
Section: Literature Review and Scope Of The Studymentioning
confidence: 99%
“…Upon analyzing transit service quality based on cluster analysis, frequency and punctuality were found to be the most important attributes, whereas accessibility was identified as a variable having limited relevance for users in Granada, Spain ( 5 ). Bajčetić et al used the quality function deployment method to identify urban public transport users’ needs related to public transport in Belgrade, and concluded that service reliability, frequency, and vehicle elements need to be considered carefully for improving the quality of public transport travel ( 17 ). Saw et al studied passenger satisfaction toward metro infrastructures, facilities, and services in the Tyne and Wear Metro, UK, and found ticket cost, general cleanliness of station, condition of station, and cleanliness inside the train to have performed inadequately from a user perspective ( 18 ).…”
Section: Literature Review and Scope Of The Studymentioning
confidence: 99%
“…Another critical factor is the purpose of the study, which determines whether it will be more theoretical or practical. (Bajčetić et al, 2018) and(Ušpalytė-Vitkūnienė et al, 2020) work in their methodology with the perception of the user and the direct participant of the traffic, while (Zhou et al, 2021) links transport quality assessment with educational activities. The theoretical framework and the complexity of defining adequate indicators are described by (Išoraite, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Passengers differently assess the advantages and disadvantages of particular transport facilities. This primarily applies to traffi c safety, control, price and conditions of transportation (comfort), as well as the time of transporting passengers to their destination (Batley, Dargay, & Wardman, 2011;Chen, Leng, Mao, & Liu, 2014;Börjesson, 2014;Guo & Wilson, 2011;Dlamini, 2011).…”
Section: Introductionmentioning
confidence: 99%